Bleeding complications during cardiac electronic device implantation in patients receiving antithrombotic therapy: is there any value of local tranexamic acid?. Issue 1 (December 2016) - Beton, Osman; Saricam, Ersin; Kaya, Hakki; Yucel, Hasan; Dogdu, Orhan; Turgut, Okan; Berkan, Ocal; Tandogan, Izzet; Yilmaz, Mehmet
Abstract Background The perioperative use of antithrombotic therapy is associated with increased bleeding risk after cardiac implantable electronic device (CIED) implantation. Topical application of tranexamic acid (TXA) is effective in reducing bleeding complications after various surgical operations. However, there is no information regarding local TXA application during CIED procedures. The purpose of our study was to evaluate bleeding complications rates during CIED implantation with and without topical TXA use in patients receiving antithrombotic treatment. Methods We conducted a retrospective analysis of consecutive patients undergoing CIED implantation while receiving warfarin or dual antiplatelet (DAPT) or warfarin plus DAPT treatment. Study population was classified in two groups according to presence or absence of topical TXA use during CIED implantation. Pocket hematoma (PH), major bleeding complications (MBC) and thromboembolic events occuring within 90 days were compared. Results A total of 135 consecutive patients were identified and included in the analysis. The mean age was 60 ± 11 years old. Topical TXA application during implantation was reported in 52 patients (TXA group). The remaining 83 patients were assigned to the control group. PH occurred in 7.7 % patients in the TXA group and 26.5 % patients in the control group (P  = 0.013). The MBC was reported in 5.8 % patients in the TXA and 20.5 % patients in control group (P  = 0.024). Univariate logistic regression analysis identified age, history of recent stent implantation, periprocedural spironolactone use, periprocedural warfarin use, perioperative warfarin plus DAPT use, cardiac resynchronization therapy, and topical TXA application during CIED implantation as predicting factors of PH. Multivariate analysis showed that perioperative warfarin plus DAPT use (OR = 10.874, 95 % CI: 2.496–47.365, P  = 0.001) and topical TXA application during CIED procedure (OR = 0.059, 95 % CI: 0.012–0.300, P  = 0.001) were independent predictors of PH. Perioperative warfarin plus DAPT use and topical TXA application were also found to be independent predictors of MBC in multivariate analyses. No thromboembolic complications was recorded in the study group. Conclusion The present study demonstrated that the topical TXA application during CIED implantation is associated with reduced PH and MBC in patients with high bleeding risk.